2016
DOI: 10.1002/chem.201602741
|View full text |Cite
|
Sign up to set email alerts
|

A Ligand That Targets CUG Trinucleotide Repeats

Abstract: The development of small molecules that can recognize specific RNA secondary and tertiary structures is currently an important research topic for developing tools to modulate gene expression and therapeutic drugs. Expanded CUG trinucleotide repeats, known as toxic RNA, capture the splicing factor MBNL1 and are causative of neurological disorder myotonic dystrophy type 1 (DM1). Herein, the rational molecular design, synthesis, and binding analysis of 2,9-diaminoalkyl-substituted 1,10-phenanthroline (DAP), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…In addition, in a liverspecific DM1 mouse model containing 960 interrupted CUG repeats, 4 decreased the levels of the transgene, likely due to the compound's inhibitory effect on d(CTG) exp transcription, improved pre-mRNA splicing defects, and reduced RNA foci formation, highlighting the compound's potential in preclinical animal models. As another example of an r(CUG) exp binding molecule, Li et al 137 designed a 1,10-phenanthroline derivative (DAP) and studied its effect by in vitro translation ( Fig. 8D and Table S1, ESI †).…”
Section: Small Molecule Inhibition Of the R(cug) Exp -Mbnl1 Complex Imentioning
confidence: 99%
“…In addition, in a liverspecific DM1 mouse model containing 960 interrupted CUG repeats, 4 decreased the levels of the transgene, likely due to the compound's inhibitory effect on d(CTG) exp transcription, improved pre-mRNA splicing defects, and reduced RNA foci formation, highlighting the compound's potential in preclinical animal models. As another example of an r(CUG) exp binding molecule, Li et al 137 designed a 1,10-phenanthroline derivative (DAP) and studied its effect by in vitro translation ( Fig. 8D and Table S1, ESI †).…”
Section: Small Molecule Inhibition Of the R(cug) Exp -Mbnl1 Complex Imentioning
confidence: 99%
“…Berglund’s group found that actinomycin D ( 20 ) and the diamidine derivatives ( 21 ) can reduce the abnormal extended CUG RNA levels. Nakatani’s group developed new small molecules targeting the CUG repeats by the rational molecular design ( 22 ). In this study, we aimed to develop a reactive small molecule with the ability of the T–T or U–U mismatch selective alkylation for DM1 research.…”
Section: Introductionmentioning
confidence: 99%
“…This was another effect of the dimerization of DAP because three to four DAP molecules were found to bind r(CUG) 9 . [39] Ta ken together,t hese analyses confirmed the most prominentb inding of DDAP with r(CUG) and r(CCG) repeats. Dimerization of DAP to DDAP was effective in increasing the affinity of the molecule to r(CUG) repeats, but not in improvings equence selectivity.T he binding of DDAP to other RNA repeats and hairpin RNAs, albeit with lower affinity,w ould be an on-negligible factor in subsequent biological assays.…”
Section: Resultsmentioning
confidence: 61%
“…The preparation of the SA chip was reported previously. [39] The amounts of r(CUG) 9 ,r (CAG) 9 ,r (CGG) 9 ,a nd r(CCG) 9 repeat immobilized on the chip surface were 327, 321, 327, and 303 RU, respectively;3 0-mer ssRNA (674 RU), 30-mer dsRNA (768 RU), and CUG20 732 RU. Binding of the ligands to the surface was analyzed by using aB IAcore T200 SPR system (GE Healthcare).…”
Section: Spr Assaymentioning
confidence: 99%
See 1 more Smart Citation